The Technology of Growing Peking Cabbage in Various Planting Schemes in Uzbekistan - Ulugbek Holmamatovich, Khurramov; Shukhrat Ismatovich, Asatov; Zafarali Toshtemirovich, Abdiev; Abror Pardayevich, Khasanov (International Journal of Psychosocial Rehabilitation, 2020)
In the Republic, cultivation of Peking cabbage has not had enough scientifically based recommendations on nutrition and placement methods, so many scientists and practitioners have been experimenting with the most delicate habitats in cultivating Peking cabbage and achieving high productivity. In our research, we obtained a 70×30 cm planting scheme as a comparative option. "Xibinskaya" sort of Peking cabbage was identified on the basis of crop yields and economic efficiency of 2016-2021, which was cultivated on 7 different schemes as a replica. The article describes the results of experiments on determining the best nutrition of Peking cabbage.